Airframe : stress analysis and sizing - Niu, Michael Chun-Yung (Conmilit Press, 1999)
1- General overview. 2- Sizing procedures. 3- External loads. 4- Material properties. 5- Structural analysis. 6- Beam stress. 7- Plates ans shells. 8- Box deams. 9- Joints and fittings. 10- Column buckling. 11- Buckling of thin sheets. 12- Shear panels. 13- Cutouts. 14- Compression panels. 15- Damage tolerant panels (tension). 16- Structural salvage and repairs. 17- Structural test setup.